Diabetic Cardiomyopathy: Clinical and Metabolic Approach - Djordjevic, Dragan B.; Koracevic, Goran; Djordjevic, Aleksandar D.; Lovic, Dragan B. (Current Vascular Pharmacology, 2021)
Background: Having in mind that diabetes mellitus (DM) and obesity are some of the greatest health challenges of the modern era, diabetic cardiomyopathy (DCM) is becoming more and more recognized in clinical practice. Main Text: Initially, DM is asymptomatic, but it may progress to diastolic and then systolic left ventricular dysfunction, which results in congestive heart failure. A basic feature of this DM complication is the absence of hemodynamically significant stenosis of the coronary blood vessels. Clinical manifestations are the result of several metabolic disorders that are present during DM progression. The complexity of metabolic processes, along with numerous regulatory mechanisms, has been the subject of research that aims at discovering new diagnostic (e.g. myocardial strain with echocardiography and cardiac magnetic resonance) and treatment options. Adequate glycaemic control is not sufficient to prevent or reduce the progression of DCM. Contemporary hypoglycemic medications, such as sodium-glucose transport protein 2 inhibitors, significantly reduce the frequency of cardiovascular complications in patients with DM. Several studies have shown that, unlike the above-stated medications, thiazolidinediones and dipeptidyl peptidase-4 inhibitors are associated with deterioration of heart failure. Conclusion: Imaging procedures, especially myocardial strain with echocardiography and cardiac magnetic resonance, are useful to identify the early signs of DCM. Research and studies regarding new treatment options are still “in progress”.
Keywords: metabolism